Microfluidics technologies and applications - Lin, Bingcheng; Basuray, S. (Sagnik).; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
S. Shoji K. Kawai Flow Control Methods and Devices in Micrometer Scale Channels L. Capretto W. Cheng M. Hill X. Zhang Micromixing Within Microfluidic Devices S. Zeng X. Liu H. Xie B. Lin Basic Technologies for Droplet Microfluidics L. Wang X. Gong W. Wen Electrorheological Fluid and Its Applications in Microfluidics J. Noh H. C. Kim T. D. Chung Biosensors in Microfluidic Chips S. Senapati S. Basuray Z. Slouka L.-J. Cheng H.-C. Chang A Nanomembrane-Based Nucleic Acid Sensing Platform for Portable Diagnostics H. Gai Y. Li E. S. Yeung Optical Detection Systems on Microfluidic Chips S. K. Njoroge H.-W. Chen M. A. Witek S. A. Soper Integrated Microfluidic Systems for DNA Analysis J. K. Osiri H. Shadpour M. A. Witek S. A. Soper Integrated Multifunctional Microfluidics for Automated Proteome Analyses C. Zhang D. van Noort Cells in Microfluidics W. Shi H. Wen B. Lin J. Qin Microfluidic Platform for the Study of Caenorhabditis elegans
Flow Control Methods and Devices in Micrometer Scale Channels, by Shuichi Shoji and Kentaro Kawai -- Micromixing Within Microfluidic Devices, by Lorenzo Capretto, Wei Cheng, Martyn Hill and Xunli Zhang -- Basic Technologies for Droplet Microfluidics, by Shaojiang Zeng, Xin Liu, Hua Xie and Bingcheng Lin -- Electrorheological Fluid and Its Applications in Microfluidics, by Limu Wang, Xiuqing Gong and Weijia Wen -- Biosensors in Microfluidic Chips, by Jongmin Noh, Hee Chan Kim and Taek Dong Chung -- A Nanomembrane-Based Nucleic Acid Sensing Platform for Portable Diagnostics, by Satyajyoti Senapati, Sagnik Basuray, Zdenek Slouka, Li-Jing Cheng and Hsueh-Chia Chang -- Optical Detection Systems on Microfluidic Chips, by Hongwei Gai, Yongjun Li and Edward S. Yeung -- Integrated Microfluidic Systems for DNA Analysis, by Samuel K. Njoroge, Hui-Wen Chen, Małgorzata A. Witek and Steven A. Soper -- Integrated Multifunctional Microfluidics for Automated Proteome Analyses, by John K. Osiri, Hamed Shadpour, Małgorzata A. Witek and Steven A. Soper -- Cells in Microfluidics, by Chi Zhang and Danny van Noort -- Microfluidic Platform for the Study of Caenorhabditis elegans,by Weiwei Shi, Hui Wen, Bingcheng Lin and Jianhua Qin.
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Microfluidics; Microfluidic devices; Electronic books